Implementation of Blended Learning for Class IX Science Learning after the Covid-19 Pandemic - Sari, Eka Ratna; Lestari, Ega; Ananda, Rifki (Yayasan Nurul Yakin Bunga Tanjung, 2022)
This study aims to determine the implementation of Blanded Learning especially in the learning of IPA after the pvemi of COVID-19 in Jambi on student learning outcomes. The object of the research is conducted at SMPN 21 Muaro Jambi and as the subject ie students of class lX of a number of 30 people. To know the implementation of the study model applied to the teacher to the students, the data collection was done by providing some questions related to the teacher and the students in the form of interview-analyzed. From the results of the analysis can be concluded that implementation applied to SMPN 21 Muaro Jambi is llanded learning, so the influence of the method has very impact on student learning outcomes on the subject of IPA. From the data obtained can conclude that students' ability in physics lessons during the blanded learning system is declining due to several obstacles experienced